ANALISIS KUALITAS LAYANAN WEBSITE BADAN KEAMANAN LAUT REPUBLIK INDONESIA MENGGUNAKAN METODE WEBQUAL 4.0 - Purnama, Hendra; Harman, Rika (LPPM Universitas Putera Batam, 2019)
This study attempts to analyze the quality of services of the Indonesian Sea Security Agency Website with the aim of knowing the difference between actual perceptions and ideal expectations of website users, in this case the Batam Society, which is measured through the WebQual 4.0 approach which is one of the website quality measurement techniques based on user perceptions . The WebQual method used in this study is WebQual version 4.0 which has been modified by adding dimensions to the quality of the user interface with the three main dimensions of WebQual 4.0, namely quality of use, quality of information, and quality of service interactions. The analysis technique uses descriptive analysis. The results of the study prove that there is a difference between the actual perceptions and ideal expectations of the Batam Society on each dimension of website service quality, this indicates that the level of quality of services of the Indonesian Maritime Security Agency has not been in line with the expectations of the Batam Community. The mapping results in the Cartesian diagram are expected to be feedback (feedback) for the website management management in developing a strategy to improve the quality of the RI Marine Security Agency website.